2015
DOI: 10.1007/s00125-015-3819-x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal three-dimensional visualisation of autoimmune diabetes by functional optical coherence imaging

Abstract: Aims/hypothesis It is generally accepted that structural and functional quantitative imaging of individual islets would be beneficial to elucidate the pathogenesis of type 1 diabetes. We here introduce functional optical coherence imaging (FOCI) for fast, label-free monitoring of beta cell destruction and associated alterations of islet vascularisation. Methods NOD mouse and human islets transplanted into the anterior chamber of the eye (ACE) were imaged with FOCI, in which the optical contrast of FOCI is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Although the exact nature of this particular contrast remains unknown, the presence of metals (such as Fe) in amyloid plaque cores, as described by Plascencia-Villa et al [23], might provide a first hint into the cause of this phenomenon. In fact, a previous study from our group showed that the contrast of the Langerhans islets in OCM images originated from the presence of Zn crystals [24]. Alternatively, this contrast could also arise from polarization effects as the plaques have been shown to have birefringent properties [25].…”
Section: Resultsmentioning
confidence: 93%
“…Although the exact nature of this particular contrast remains unknown, the presence of metals (such as Fe) in amyloid plaque cores, as described by Plascencia-Villa et al [23], might provide a first hint into the cause of this phenomenon. In fact, a previous study from our group showed that the contrast of the Langerhans islets in OCM images originated from the presence of Zn crystals [24]. Alternatively, this contrast could also arise from polarization effects as the plaques have been shown to have birefringent properties [25].…”
Section: Resultsmentioning
confidence: 93%
“…For instance, it has been shown that a modification of the vascularization is associated with the early onset of both type I and II diabetes [2][3][4][5]. Using functional optical coherence imaging (FOCI), we found that there is a strong correlation between the increasing inflammation of the islets and the density of their vascular network [6]. In addition, there are indications that the glucose intolerance observed in aged mice is due to a vascular impairment rather than β-cell defect [7].…”
Section: Introductionmentioning
confidence: 87%
“…For pancreas imaging, 6 to 8 B-scans were taken to perform averaging depending on the stabilization achieved, whereas for ACE imaging, 8 B-scans were averaged. Extraction of the islet and vascular volumes were done using algorithms described in previous papers [6,30]. The vascular density is defined as the ratio between the vascular volume and the islet volume.…”
Section: Data Processingmentioning
confidence: 99%
See 2 more Smart Citations